PENURUNAN KADAR CO2 PADA BIOGAS DENGAN ABSORBSI NaOH TERHADAP KECEPATAN RAMBAT API - As’adi GA; Nasrul Ilminnafik; Ahmad Syuhri (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2014)
Biogas is produced from the fermentation process and generate gases: CH4, CO2, H2, N2, O2, and H2S. The biogas content on there are still many impurities (inhibitors) in affecting the quality of the biogas biogas, one of which is CO2. Carbon dioxide is a molecule that can inhibit and decrease the rate of the combustion reaction, because the carbon dioxide would disrupt the chain of chemical reactions of combustion, so the chemical reaction of combustion is inhibited. This study was to determine the effect of variations in the concentration and duration of contact NaOH to the reduction of CO2 levels shown in the figure the distance between the flame propagation speed of propagation of fire and flame. Observations carried out experiments with burning stoichiometric mixture (methane and air) that has been purified in the combustion chamber Helle-Shaw Cell 1cm x 20cm x 60cm. The results showed that the concentration and contact time can reduce the levels of CO2 in the biogas yield faster flame propagation speed. Keywords: Cepat Rambat Api, Karbon dioksida, Konsentrasi NaOH, Waktu kontak